Curriculum as lived : currere, mindfulness, and nonviolent companionship - Wang, Hongyu; Flory, Jo (Lived experience, nonviolence, and curriculum studies, 2025)
There is a strong sense of existential crisis in US education. In a time that is discouraging, disturbing, and daunting, Curriculum as Lived: Currere, Mindfulness, and Nonviolent Companionship features an uplifting collection of educators' writings, as they expand their interior space, diving into the individual and collective psyche to engage in shadow work for healing and revitalization. Heartfelt, profoundly moving, and inspirational, these educators' journeys in curriculum as lived are embodied, emergent, and extraordinary in their crafted capacities for holding the tension between the dark and the light to open a crack for breathing in fresh new air. Three forms of experiential studies and self-education are demonstrated in this collection: currere and autobiographical inquiry, mindfulness and mindful relationships, and nonviolent companionship. Grounding education in experiential understanding and integrative cultivation, beyond simplistic storytelling, these authors courageously make polyphonic lines of movement toward personal and social transformation, and their inner work and relational attunement are full of twists and turns. Working from within is the cornerstone for non-controlling relationality, in the spirit of contemplation, compassion, and companionship as well as of the struggles against psychic and social violence in various forms. Affirming the central role of interconnectedness, this book is a testimony to the integrative power of nonviolence. Professors, graduate students, K-20 teachers, and curriculum and instruction leaders at various levels in the fields of curriculum studies, teacher education, nonviolence and peace education, and educational foundations will welcome this book. It also serves as a text for upper-level undergraduate courses in education and nonviolence studies.